ANALISIS AGLOMERASI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI TERKONSENTRASINYA LEMBAGA PENDIDIKAN TINGGI DI PULAU JAWA - Tutus Alun Asoka Sakti (Journal of Indonesian Economy and Business (JIEB), 2007)
This paper seeks to find out agglomeration of higher education institutions in Java. Using logistic regression analysis, it will examine to what extent some key variables predicting and explaining why these institutions tended to cluster in certain regions. (1) Number of labor force, (2) Number of school age, (3) GNP, (4) Technology, (5) Economic activity, (6) Infrastructure and (7) Existance of public higher education institution.The results show that spatial pattern of higher education institutions tended to be similar to those of large and medium scale enterprises. Higher education institutions agglomerated overwhelmingly around city centre while large and medium enterprises preferred to cluster around the outskirtThis paper seeks to find out agglomeration of higher education institutions in Java. Using logistic regression analysis, it will examine to what extent some key variables predicting and explaining why these institutions tended to cluster in certain regions. (1) Number of labor force, (2) Number of school age, (3) GNP, (4) Technology, (5) Economic activity, (6) Infrastructure and (7) Existance of public higher education institution.The results show that spatial pattern of higher education institutions tended to be similar to those of large and medium scale enterprises. Higher education institutions agglomerated overwhelmingly around city centre while large and medium enterprises preferred to cluster around the outskirt